2020
DOI: 10.1002/jhet.3941
|View full text |Cite
|
Sign up to set email alerts
|

PPAR gamma targeted molecular docking and synthesis of some new amide and urea substituted 1, 3, 4‐thiadiazole derivative as antidiabetic compound

Abstract: The PPAR‐γ agonist enhances the insulin sensitivity and avoids the disorganized hyperglycemic by promoting the insulin guided cellular uptake of blood glucose. Therefore, in the present work PPAR‐γ has chosen as the target for the molecular docking study to design an effective agonist of the same. By this research work an effort has been made to prepare amide and urea series of 1, 3, 4‐thiadiazole derivatives as 4‐substituted‐N‐(5‐(4‐(1‐piperidino)1‐piperidinyl)‐1,3,4‐(2‐thiadiazolyl)benzamide (4a‐f) and 1‐(4‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…antimicrobial [31][32][33], antidiabetic [34][35][36], antitubercular, [37][38], antiviral [39][40] and anticancer activities [41][42][43]. For example, [N-(4-acetyl-4,5-dihydro-5-methyl-5-phenyl-1,3,4thiadiazol-2-yl)acetamide] (D in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…antimicrobial [31][32][33], antidiabetic [34][35][36], antitubercular, [37][38], antiviral [39][40] and anticancer activities [41][42][43]. For example, [N-(4-acetyl-4,5-dihydro-5-methyl-5-phenyl-1,3,4thiadiazol-2-yl)acetamide] (D in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated molecular docking with PPAR‐γ targeting and the synthesis of several novel 1,3,4‐thiadiazole compounds with amide and urea substitution as antidiabetic agents. Compounds 73 and 74 containing the electron donating methyl substituted aromatic group exhibited potent PPAR‐γ % inhibition with 87.5 % and 89.7 % rise in Blood glucose levels and Target proteins and synthetic derivatives are actively involved in binding, according to a molecular docking study, and there is a strong connection between these results with biological activity [85] . Hameed SA et al.…”
Section: Discussionmentioning
confidence: 98%
“…Compounds 73 and 74 containing the electron donating methyl substituted aromatic group exhibited potent PPAR-γ % inhibition with 87.5 % and 89.7 % rise in Blood glucose levels and Target proteins and synthetic derivatives are actively involved in binding, according to a molecular docking study, and there is a strong connection between these results with biological activity. [85] Hameed SA et al investigated a number of new derivatives of 5-furyl-1,3,4-thiadiazol-2-imine, designing and synthesizing those with favourable physiochemical properties and further screened for α-amylase activity. Compound 75 exhibited potent % inhibitory activity with 94.55 � 1.80 % as compared to standard acarbose 93.58 % inhibition and formed H-bonds with Ala198, His201, Ala198 with α-amylase binding pocket.…”
Section: Pharmacological Characteristics Of Thiadiazole Analoguesmentioning
confidence: 99%
“…44 These data are also confirmed in numerous other works. [45][46][47][48] For example, Parvesh Singh 48 reported on the synthesis of new 1,3,4-thiadiazole derivatives, among which a compound (Fig. 3, compound C) was identified that showed a high degree of inhibition of α-glucosidase and α-amylase with an IC value of 2.59 μM, which is ∼1.5 and 14 times higher than that of the standard inhibitor acarbose.…”
Section: Introductionmentioning
confidence: 99%